Response of garlic to zinc, boron and poultry manure application - Nasreen, S; Yousuf, MN; Mamun, ANM; Brahma, S; Haquc, MM (Bangladesh Journal of Agricultural Research, 2010)
Response of garlic (var. BARI Garlic-2) to zinc, boron, and poultry manure application along with a blanket dose of 150 kg N, 50 kg P, 100 kg K, and 40 kg S/ha was evaluated through field trials in the Grey Terrace Soil under AEZ 25 (Level Barind Tract) at Spices Research Centre, Bogra during two consecutive rahi seasons (2005-2006 and 2006-2007). Application of zinc, boron, and poultry manure significantly had increased plant height, number of leaves/plant, cloves/bulb, diameter, and weight of bulb and yield/ha in both years. The highest bulb yields of 6.10 t/ha in 2005-2006 and 6.23 t/ha in 2006-2007 were obtained from the Zn5B1 kg/ha plus 5 t/ha poultry manure treatment and it was significantly higher over all other treatments. Next to it, the treatment Zn5B1 kg/ha plus 2.5 t/ha poultry manure gave the highest bulb yield (5.99 t/ha in 2005-2006 and 6.00 t/ha in 2006-2007). The highest gross margin of Tk. 230594/ha in 2005-2006 and Tk. 234095/ha in 2006-2007 along with lower marginal rate of return (65 and 163%) were obtained with Zn5B1 kg/ha plus 5 t/ha poultry manure treatment. This treatment was not economical because of the higher cost involvement. Application of Zn at 5 kg/ha along with blanket dose of N, P, K, and S fertilizers would be profitable (MRR of 5650% in 2005-2006 and 1562% in 2006- 2007) for garlic cultivation in the Gray Terrace Soil of Shibgonj, Bogra. Key Words: Garlic; zinc; boron; poultry manure. DOI: 10.3329/bjar.v34i2.5795 Bangladesh J. Agril. Res. 34(2): 239-245, June 2009